Teachers’ perceptions of the use of flipped learning approach in learning grammar - Aisyah Hanum, Abu Bakar; Noor Azlinda, Zainal Abidin; Zuraina, Ali; Nursyaheedah, Muhammad Isa; Nor Suhardiliana, Sahar (Global Business and Social Entrepreneurship Resources, 2018)
Flipped learning approach in the teaching and learning is defined as an inverted method, in which activities such as the delivery of the content are done at homes, and activities normally constituting homework and practices are done during class time (Bergmann & Sams, 2012; Sohrabi & Iraj, 2016). The method is not only applicable to tertiary level students but also to primary and secondary school students. With the help of technology, it can also assist in English classes, particularly in reading, writing, listening and speaking and also grammar knowledge. This study aimed to examine teachers’ perceptions towards the application of flipped learning approach in preparing the students for Get into Grammar (GIGvaganza) program and to identify the problems that hindered the maximum use of flipped learning approach in a classroom. This study employed quantitative data enquiry involving 51 teachers from three districts in Pahang. The results showed that the approach appeared to play a significant role in motivating the students to learn and apply the grammar knowledge as well as to engage in the activities conducted. The findings implied that flipped learning approach is very much important in assisting the students to be active in English classes, particularly in grammar lessons and should also be applied to other skills.